The Biofuel industry and its Effect on National Development (Ecuador) (Revista Científica Ciencias Naturales y Ambientales, 2015)
One of main problems that face the world is meeting the high energy demands of modern industrialized global society of the XXI century; especially by ensuring that they are developed in a sustainable and friendly way with the environment. In this context the use of alternative energies, including biofuels, today that Ecuador walks towards the diversification of the energy matrix, looking energize your productive matrix. The is aim of this research to review, analyze and discuss a number of technical, economic and social-environmental documentation, in order to have more information regarding the effect that generates the biofuels agroindustry in the development of the Ecuador. In the Ecuador for more than one decade both the guild of sugar cane farming, oil palm such as the agro-industrial and the State, seek consensus regarding progress in biofuels, all time that is insists in improve the agroindustry of the chain productive both of the cane of sugar for the bioethanol,as the palm oil to the biodiesel. Despite advances in technical agro, there is apparent skepticism, given that failure for example, further spread of energy crops such as sugarcane in order to meet the demand national of bioethanol that is required to generate a blend of up to 10%.
Keywords: Alternative energies; biofuels; energy crops work; environment